Age and Ageing in Contemporary Speculative and Science Fiction, edited by Sarah Falcus and Maricel Oró-Piqueras: Reviewed by Ingvil Hellstrand - Hellstrand, Ingvil (Age, Culture, Humanities: An Interdisciplinary Journal, 2023)
--- Submitted: 24 October 2023 Published: 22 December 2023